Wayang dan Perkembangannya - Soetarno, Soetarno (Institut Seni Indonesia Yogyakarta, 2010)
Shadow Puppet Theatre and Its Development. Wayang (shadow puppet show) has developed and changed in forms, performing techniques, types, and details. The wayang show refers to the values of life and is an interpretation of life that is actualized through the art of shadow play puppetry. Because of it, wayang show presents a number of values, the ones that are related to various matters that are revealed in real forms as well as the ones that are associated with the customs and manners of the society. In addition to other objectives, such as providing information, delivering propaganda, critisizing the social life, entertaining and so on, each show is hoped to be able to deliver motivating messages to the audiences so that they can get satisfying aesthetics experience.The show is a value resource that can express a message artistically and aesthetically.Javanese Wayang Kulit Purwa still exist in the era of globalization for it is not merely seen from its visual or aesthetical aspects, but also the meanings behind it. For Javanese people, wayang functions as a performance, a life teaching, and a life arrangement. For that reason, in 2003, UNESCO declared wayang as an intangible world heritage. keywords: puppet theatre, wayang, kelir